MINDS AND MORALS. - Sawyer, Sarah (Philosophical Issues, 2014)
In this paper, I argue that an externalist theory of thought content provides the means to resolve two debates in moral philosophy. The first--that between judgement internalism and judgement externalism--concerns the question of whether there is a conceptual connection between moral judgement and motivation. The second--that between reasons internalism and reasons externalism--concerns the relationship between moral reasons and an agent's subjective motivational set. The resolutions essentially stem from the externalist claim that concepts can be grasped partially, and a new moral theory, which I call 'moral externalism', emerges.